Activation of TLR-pathway to induce host Th1 immune response against visceral leishmaniasis: Involvement of galactosylated-flavonoids. Issue 7 (July 2022) - Pradhan, Supratim; Snehlata,; Manna, Debolina; Karmakar, Subir; Singh, Manoj Kumar; Bhattacharya, Arijit; Mukherjee, Budhaditya; Paul, Joydeep
Abstract: Immunotherapeutic strategies against visceral leishmaniasis (VL) are pertinent because of the emergence of resistance against existing chemotherapy, coupled with their toxicity and high costs. Various bioactive components with potential immunomodulatory activity, such as alkaloids, terpenes, saponins, flavonoids obtained primarily from medicinal plants, have been screened against different disease models. Reports suggested that glycans containing terminal β-galactose can skew host immune response towards Th1 by engaging TLRs. In this study, two synthesized terminal galactose-containing flavones, Quercetin 3-d -galactoside (Q-gal) and Kaempferol 3-O-d -galactoside (K-gal), are profiled in terms of inducing host protective Th1 response in both in vitro & in vivo animal models of experimental VL individually against antimony-resistant & antimony-susceptible Leishmania donovani. Further, we explored that both Q-gal and K-gal induce TLR4 mediated Th1 response to encounter VL. Molecular docking analysis also suggested strong interaction with TLR4 for both the galactosides, with a slightly better binding potential towards Q-gal. Treatment with both Q-gal and K-gal showed significant antileishmanial efficacy. Each considerably diminished the liver and splenic parasite burden 60 days after post-infection (>90% in AG83 infected mice and >87% in GE1F8R infected mice) when administered at a 5 mg/kg/day body-weight dose for ten consecutive days. However, the treatments failed to clear the parasites in the TLR4 deficient C3H/HeJ mice. Treatment with these compounds favors the elevation of TLR4 dependent host protective Th1 cytokines and suppression of disease-promoting IL-10. Q-gal and K-gal also triggered sufficient ROS generation in macrophages to kill intracellular parasites directly. Highlights: Galactosilated flavonoids treatment clears in-vivo drug-resistant Leishmania donovani infection. Quercetin 3-d -galactoside (Q-gal) & Kaempferol 3-O-d -galactoside (K-gal) induce host TLR4 pathway. These flavonoids up-regulate Th1 cytokines and suppress the disease-promoting IL-10. TLR4 deficient C3H/HeJ mice are unresponsive towards Q-gal and K-gal treatment. Abstract : Antileishmanial, TLR-4, Galactosylated-Flavonoids, Reactive oxygen species, Th1 response, Visceral leishmaniasis.